DESIGN AND DEVELOPMENT OF A POSTCARD-INTEGRATED AUGMENTED REALITY APPLICATION FOR EDUCATIONAL EXPLORATION OF LOMBOK ISLAND TOURIST ATTRACTIONS - Regania Pasca Rassy; Lalu Romy Rahmad Amarta Putra; Muhammad Rifkyandryan Rustanto; Nazila Imkani; Risfanda Audiarrahman Charisma; Zahra Tri Lusiana (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2026)
Indonesia possesses diverse tourism destinations, including Lombok Island, known for its natural landscapes and cultural heritage. However, the introduction of local tourism knowledge to elementary school students remains limited, as textbooks and two-dimensional images predominate, which are less engaging for digital-age learners. This study aims to design and develop an augmented reality-based mobile application to support the educational exploration of tourist attractions on Lombok Island. The development process adopted the Multimedia Development Life Cycle model, which comprises the concept, design, material collection, assembly, testing, and distribution stages. The application visualizes prominent destinations such as Mount Rinjani, Gili Trawangan, and Sade Village through interactive three-dimensional objects accompanied by concise educational information. Functional testing results indicate that the application operates effectively on mobile devices and provides an interactive learning experience. The findings suggest that integrating Augmented Reality technology into local geography and cultural education enhances student engagement and understanding. The application can serve as an innovative digital learning medium to promote awareness and appreciation of regional heritage among elementary school students.